2018
DOI: 10.3126/mjsbh.v17i2.20290
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cesarean Section Using Robson’s 10-Group Classification at a Tertiary Level Hospital in Nepal

Abstract: Introduction: Obstetric Services commenced at the teaching institute where this study was conducted from Aug 2012. Hence, a review of the data of C-section in this hospital is needed for standardisation of the obstetric services in terms of the rate of C-section, its various clinical indications and maternal and fetal outcomes.Methods: This is a retrospective study carried out over a period of 5 years from Aug 13, 2012 to Aug 11, 2017. All hospital deliveries conducted during the study period were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The present study revealed that the magnitude of CS was found to be 32.5 % indicated that almost twice more than the WHO recommendation of 10–15 % [ 6 ]. The finding was slightly higher than studies conducted in Felegehiwot referral hospital, Amhara region, Northwest Ethiopia 25.4 % [ 16 ], Nepal 22.6% [ 23 ], Vietnam 26.2 %, [ 26 ], Sri Lanka, India 25 % [ 11 ], Mizan-Aman general hospital, Southwest Ethiopia 21 % [ 25 ] and Shire, Tigray region, Northern Ethiopia 20.2 % [ 15 ]. The result was nearly consistent with studies conducted in North Wollo Zone public hospitals, Amhara region, Northeast Ethiopia 30.9 % [ 17 ], Hawassa university referral hospital, southern Ethiopia 32.8 % [ 18 ], and Jugal hospital, Harari Regional State, eastern Ethiopia 29.7 % [ 28 ].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The present study revealed that the magnitude of CS was found to be 32.5 % indicated that almost twice more than the WHO recommendation of 10–15 % [ 6 ]. The finding was slightly higher than studies conducted in Felegehiwot referral hospital, Amhara region, Northwest Ethiopia 25.4 % [ 16 ], Nepal 22.6% [ 23 ], Vietnam 26.2 %, [ 26 ], Sri Lanka, India 25 % [ 11 ], Mizan-Aman general hospital, Southwest Ethiopia 21 % [ 25 ] and Shire, Tigray region, Northern Ethiopia 20.2 % [ 15 ]. The result was nearly consistent with studies conducted in North Wollo Zone public hospitals, Amhara region, Northeast Ethiopia 30.9 % [ 17 ], Hawassa university referral hospital, southern Ethiopia 32.8 % [ 18 ], and Jugal hospital, Harari Regional State, eastern Ethiopia 29.7 % [ 28 ].…”
Section: Discussionmentioning
confidence: 64%
“…The explanatory variables for this study were includes; gravidity, categorized as ‘primigravida’, ‘multigravida’ and ‘grand multigravida’; parity, categorized as ‘nulliparous’ or ‘multipara’, ‘Grand multiparous’; fetal lie/presentation, categorized as ‘breech’ or ‘cephalic’, lie ‘transverse or oblique’; onset of labour, categorized as ‘spontaneous’, ‘induced or CS before labour’; malpresentation, categorized as ‘Yes’ and ‘No’; multiple pregnancies, categorized as ‘singleton’ or ‘multiple’; Gestational age, classified as ‘term > 37weeks’, ‘preterm < 37 weeks’ and ‘post-term > 42 weeks’ new-born birth weight; newborn birth weight, categorized as ‘normal birth weight (2500-4000gm)’, ‘low birth weight (< 2500gm)’, ‘macrosomia (> 4000gm)’; previous history of CS, categorized as ‘Yes’ and ‘No’[ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this sense also studies from elsewhere; the caesarean section rate, its indications were calculated and grouped according to Robson’s 10-group classification; The most common indications were previous caesarean section (25.4%), fetal stress (14.3%), and breech presentation (10.3%). 26 , 27 However, results differ from those obtained by Makhanya et al, 22 where the main indications for CS were fetal distress (36.5%) and cephalo-pelvic disproportion (26.8%).…”
Section: Discussion Of Study Key Findingsmentioning
confidence: 77%